Sustainable agri-food investments require multi-sector co-development of decision tools - Negra, C.; Remans, R.; Attwood, S.; Jones, S.; Werneck, F.; Smith, A. (Elsevier, 2020)
Global targets, such as the UN Sustainable Development Goals, and private sector commitments, such as deforestation-free supply chains, are stimulating growing demand for sustainable investment opportunities in the food and agriculture sector. Yet, the supply of such opportunities has been slow to materialize despite a proliferation of impact funds and other sustainability-focused funders seeking to direct global capital flows into the sector. This can be explained, in part, by the heterogeneous, multi-layered, and fragmented nature of agricultural production systems and food value chains and the poorly developed knowledge systems available to inform new types of investment. The volume of sustainability-oriented investment in the food and agriculture sector is likely to be hampered by the absence of a robust scientific evidence base and well-designed tools (e.g. indices and other benchmarking mechanisms) for harnessing knowledge to investment decision processes. At present, indicatorbased tools for incorporating sustainability into agricultural value chains are being developed without adequate engagement by scientists. Collaborative co-development of decision tools by researchers and corporate and financial actors, that draws upon their distinct needs and knowledge sets, can improve the utility of these tools for real-world application (e.g. assessing non-financial returns; mitigating reputational risk). This paper proposes new requirements and strategies for the scientific community to contribute to co-development of science-based indicators and other decision tools that better enable agri-sector companies and investors to integrate food system sustainability considerations into management and capital allocation. It will present early lessons from multi-sector engagement in construction of indices, such as the Agrobiodiversity Index (ABDI), and review new modes for research institutions to engage with private sector partners.